Causation, Vitalism, and Hume - McCall, Bradford ca. 21. Jh. (Philosophy & theology, 2017)
Causation has troubled philosophers since the time of Aristotle, and they have sought to clarify the concept of causation because of its implications for other philosophical issues. The most radical change in the meaning of “cause” occurred during the late seventeenth, in which there emerged a strong tendency to understand causal relations as instantiations of deterministic laws. In this essay, I note how early modern philosophers, eminently apparent in Hume, reacted to the notion of vitalism and posited a conception of causation in which it and determinism became virtually equivalent, which thereby denied any sort of vitalistic impulse within matter.